Copper and Lead Ions Removal by Electrocoagulation: Process Performance and Implications for Energy Consumption - Aji Prasetyaningrum; Dessy Ariyanti; Widayat Widayat; Bakti Jos (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Electroplating wastewater contains high amount of heavy metals that can cause serious problems to humans and the environment. Therefore, it is necessary to remove heavy metals from electroplating wastewater. The aim of this research was to examine the electrocoagulation (EC) process for removing the copper (Cu) and lead (Pb) ions from wastewater using aluminum electrodes. It also analyzes the removal efficiency and energy requirement rate of the EC method for heavy metals removal from wastewater. Regarding this matter, the operational parameters of the EC process were varied, including time (20−40 min), current density (40−80 A/m2), pH (3−11), and initial concentration of heavy metals. The concentration of heavy metals ions was analyzed using the atomic absorption spectroscopy (AAS) method. The results showed that the concentration of lead and copper ions decreased with the increase in EC time. The current density was observed as a notable parameter. High current density has an effect on increasing energy consumption. On the other hand, the performance of the electrocoagulation process decreased at low pH. The higher initial concentration of heavy metals resulted in higher removal efficiency than the lower concentration. The removal efficiency of copper and lead ions was 89.88% and 98.76%, respectively, at 40 min with electrocoagulation treatment of 80 A/m2 current density and pH 9. At this condition, the speciﬁc amounts of dissolved electrodes were 0.2201 kg/m3, and the energy consumption was 21.6 kWh/m3. The kinetic study showed that the removal of the ions follows the first-order model.